CASE REPORT: TREATMENT OF UROLITHIASIS IN A PREGNANT MIXED BREED CAT - Arni Safitri, Gusti Putu; Dewi, Ida Ayu Dian Kusuma; Suartha, I Nyoman (Buletin Veteriner Udayana, 2025)
Urolithiasis is a disease caused by the presence of stones/crystals in the urinary tract. This report aims to diagnose and treat urolithiasis in pregnant cats. A 2-year-old, mixed-breed pregnant cat weighing 3.7 kg presented with complaints of bloody urine and difficulty urinating. Physical examination revealed reddish genital mucosa and distended urinary bladder. Macroscopic examination revealed yellowish-brown urine, an ammonia-like odor, and sediment. Microscopically, struvite and red blood cells were found in the urine. A dipstick test showed a pH of 8.0, leukocytes 3+, protein 3+, bilirubin +, erythrocytes 4+, and a specific gravity of 1.010. Ultrasonography showed wall thickening and hyperechoic color, indicating struvite crystals in the urinary bladder. Routine hematology examination showed lymphocytopenia and granulocytopenia. Urine culture revealed Staphylococcus sp. and Hafnia sp. Based on the overall examination results, the animal was diagnosed with urolithiasis. Causative therapy was given in the form of Cefixime trihydrate, Kejibeling®, and Cystaid Plus®. Supportive therapy was given with Livron B Plex® and feeding with Royal Canin® Urinary S/O. After 7 days of treatment, the patient was able to urinate with clear yellow urine. The cat should be provided with regular drinking water, a separate litter box, and separated from other cats during pregnancy.